2011
DOI: 10.2109/jcersj2.119.563
|View full text |Cite
|
Sign up to set email alerts
|

Processing of polymer-derived porous SiC body using allylhydridopolycarbosilane (AHPCS) and PMMA microbeads

Abstract: A simple method for making a porous SiC body through a polymeric route at one firing processing was demonstrated by the sacrificial filler template approach. By incorporating sacrificial pore-forming plastic powder, PMMA microbeads, into liquid preceramic polymer, AHPCS, and losing it after the polymer was hardened, a preceramic porous body was formed. As a consequence of systematic examination of the effects of particle size and mixture ratio of the powder, an AHPCS-derived porous SiC body was reproducibly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Micrographs (a) and (b) show the microstructures after the first and sixth densification process, respectively. In micrograph (a), spherically-shaped pores, similar to those formed in monolices, 16) were observed among the fibers. This suggests that the pore-forming powder could well penetrate into the congested fiber interspaces in the unidirectional fiber sheets.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Micrographs (a) and (b) show the microstructures after the first and sixth densification process, respectively. In micrograph (a), spherically-shaped pores, similar to those formed in monolices, 16) were observed among the fibers. This suggests that the pore-forming powder could well penetrate into the congested fiber interspaces in the unidirectional fiber sheets.…”
Section: Resultsmentioning
confidence: 87%
“…Using a systematic research method, the optimum condition for slurry preparation was found. 16) While pyrolyzed products are normally formed with a lot of cut-through crack initiation and consequently break into pieces even when mixed with some inert particles, we were able to produce a stable polymer-derived porous body using our process.…”
Section: )6)mentioning
confidence: 91%
See 1 more Smart Citation
“…[9] Activated carbon aerogel coated with a sol-gel silica layer has been used to synthesize SiO 2 /C, which converts into SiC/C porous composites upon high-temperature carbothermal reduction. [11,12] Using a sacrificial filler approach Kotani et al [13] prepared a macroporous SiC body through pyrolysis of a polycarbosilane and PMMA microbeads. Numerous reports have been published by Colombo et al about direct blowing of preceramic polymers to SiOC and SiC foams.…”
Section: Introductionmentioning
confidence: 99%
“…1)14) Recently, various processing methods for producing porous SiC ceramics using preceramic polymers have been developed because of the advantages of polymer processing routes compared to ceramic powder processes. The advantages include (i) low processing temperatures compared to high temperatures required for the sintering of ceramic powders; 14)16) (ii) use of low cost plastic forming techniques such as compression molding, injection molding, and extrusion; 17),18) (iii) easy handling before heat treatment since preceramic polymers can effectively bind the parts at low temperatures; 15), 19) (iv) utilization of unique polymeric properties that cannot be found in ceramic powders such as appreciable plasticity, in situ gas evolution ability, appreciable CO 2 solubility, and appreciable solubility of preceramic polymers in organic solvents; 20)23) and (v) ceramic products containing a unique combination of polymer-like nano structures with ceramic-like properties, such as good hardness, creep resistance and oxidation resistance.…”
mentioning
confidence: 99%